IDENTIFIKASI MORFOLOGI KEPADATAN SPECIES LALAT DAN UPAYA PENGENDALIAN DI PUSAT PASAR BERASTAGI KABUPATEN KARO TAHUN 2019 - Likasi Emita Sebayang; jernita Sinaga (Jurnal Ilmiah PANNMED (Pharmacist, Analyst, Nurse, Nutrition, Midwivery, Environment, Dentist), 2021)
Identification of species of flies can see the characteristics of the body shape of flies by looking at organs identified by using a microscope and identification key book of adult fly species using Borror identification keys, and literature search by examining books and articles about flies, guidelines for entomological surveys. The body of flies is usually short, small and slender life flies are very adaptable to the surrounding air. Knowing the fly's morphology and measuring the density of flies by identifying the species of flies in this study is one of the efforts to determine the level of density and population distribution of fly species in the Berastagi market. The fly is one of the insects of the Order listed which is a member of the Hexapoda class or the insect has the largest number of genera and species which covers 60-70% of all Anthropod species or 60,000 - 100,000 species of flies.